Advances in cryopreservation of alginate-encapsulated stem cells and analysis of cryopreservation outcome - Gryshkov, O.; Mutsenko, V.; Tymkovych, M.; Tarusin, D.; Sirotinskaya, V.; Braslavsky, I.; Аврунін, О. Г.; Glasmacher, B. (Інститут проблем кріобіології та кріомедицини НАН України, 2018)
Advances in cryopreservation of alginate-encapsulated stem cells and analysis of cryopreservation outcome is described.
Keywords: Cryopreservation; alginate-encapsulated structures; stem cells; image analysis